Leibniz : perception, apperception, and thought - McRae, Robert F. (University of Toronto Press, 1976)
This book attempts to give coherence to the elements of Leibniz's epistemology by seeking to determine what he meant when, on three occasions and each time without explanation, he said that thought and the faculty of understanding are the products of the conjoining of apperception and perception.